2020
DOI: 10.3390/ijms21082698
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Long Noncoding RNAs as Therapeutic Targets in Renal Fibrosis

Abstract: Many studies have made clear that most of the genome is transcribed into noncoding RNAs, including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), both of which can affect different cell features. LncRNAs are long heterogeneous RNAs that regulate gene expression and a variety of signaling pathways involved in cellular homeostasis and development. Several studies have demonstrated that lncRNA is an important class of regulatory molecule that can be targeted to change cellular physiology and function. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Additionally, ODNs with consensus binding sequences for specific transcription factors have been studied regarding the regulation of gene expression in living cells [ 32 ]. Decoy ODNs are transcription repressors, that also bind to the transcription factor, inhibiting gene expression by occupying the DNA binding site of the transcription factor in the nucleus [ 54 ]. Thus, this study confirmed the regulation of autophagy expression with STAT3 decoy ODNs in a UUO mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ODNs with consensus binding sequences for specific transcription factors have been studied regarding the regulation of gene expression in living cells [ 32 ]. Decoy ODNs are transcription repressors, that also bind to the transcription factor, inhibiting gene expression by occupying the DNA binding site of the transcription factor in the nucleus [ 54 ]. Thus, this study confirmed the regulation of autophagy expression with STAT3 decoy ODNs in a UUO mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, XLOC-2222497 and AKR1C1 were both highly expressed on day 32 of pregnancy, which was consistent with their positive regulation. lncRNAs can regulate the expression of target genes via a variety of mechanisms [74]. Because XLOC-2222497 was mainly located in the nucleus, there were two possible molecular mechanisms underlying the regulation of XLOC-2222497 on AKR1C1: (1) XLOC-2222497 increased the stability of AKR1C1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Not only in its origin, the transcriptomic, and epigenetic profiles, as well as the impact of the inter-cell matrix are all involved in uterine fibroid growth [2]. Additionally, microRNA plays a role in regulating uterine fibroid pathogenesis [3].…”
Section: Introductionmentioning
confidence: 99%